Study of the oscillation modes in a Symmetric Physical Pendulum using the effective potential - Hernandez Rosso, Jose Fernando; Maya Taboada, Héctor Roger (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In this paper we present a unified study of the dynamics of the symmetrical physical pendulum in the phase space of the different oscillation modes presented in this system: plane mode, elliptic mode and conic mode, using an effective potential that will depend on the nutation coordinate and also depends parametrically on the energy and angular momentum of the system. We also present a formal deduction of the Allais approximation for the apsidal precession of the symmetrical physical pendulum using the theory of small oscillations around the steady motion or conic oscillation mode.